Effects of early ivabradine therapy in patients with acute heart failure: A meta-analysis and systematic review - Nuraini, Yulianna Cahya; Irnizarifka, Irnizarifka; Prameswari, Hawani Sasmaya; Simangunsong, Robby Martin (Universitas Brawijaya, 2025)
BACKGROUND: Although ivabradine is the agent of choice for reducing heart rate, its use in acute heart failure patients remains unclear. OBJECTIVES: To evaluate the potential of in-hospital ivabradine administration in reducing heart rate, the risk of rehospitalization, mortality, and clinical profile in acute heart failure patients using a meta-analysis approach. METHODS: The study was designed as a meta-analysis conducted from August to September 2024. We selected several database sources for the search strategy, including PubMed, Google Scholar, ProQuest, British Medical Journal, and American Journal of Cardiology. Data on the outcomes of ivabradine treatment compared to standard therapy were collected to determine cumulative point estimates. For statistical analysis, we used the Mantel–Haenszel test for categorical data or inverse variance for continuous data. RESULTS: We included 11 articles in the study. Our findings indicated that, in comparison to the standard therapy group, the ivabradine group was associated with improvements in resting heart rate, a reduction in the risk of rehospitalization, a decrease in cardiovascular mortality, a reduction in all-cause mortality, a shorter length of stay, improvements in New York Heart Association (NYHA) classification, better Left Ventricular Ejection Fraction (LVEF), and improved B-type Natriuretic Peptide (BNP) / N-terminal pro b-type Natriuretic Peptide (NT-proBNP) levels. CONCLUSION: In conclusion, this study has revealed the beneficial effects of using ivabradine for the treatment of acute heart failure. TRANSLATE with x English Arabic Hebrew Polish Bulgarian Hindi Portuguese Catalan Hmong Daw Romanian Chinese Simplified Hungarian Russian Chinese Traditional Indonesian Slovak Czech Italian Slovenian Danish Japanese Spanish Dutch Klingon Swedish English Korean Thai Estonian Latvian Turkish Finnish Lithuanian Ukrainian French Malay Urdu German Maltese Vietnamese Greek Norwegian Welsh Haitian Creole Persian Â Â TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster Portal Back